The Effects of Alda-1 Treatment on Renal and Intestinal Injuries After Cardiopulmonary Resuscitation in Pigs - Yu, Qian; Gao, Jianbo; Shao, Xuebo; Lu, Wei; Chen, Linling; Jin, Lili (Frontiers in Medicine, 2022)
Aim: After successful cardiopulmonary resuscitation (CPR), most survivors will develop acute kidney injury and intestinal barrier dysfunction, both of which contribute to the poor outcomes of cardiac arrest (CA) victims. Recently, the aldehyde dehydrogenase 2 (ALDH2) agonist, Alda-1 was shown to effectively alleviate regional ischemia/reperfusion injury of various organs. In the present study, we investigated the effects of Alda-1 treatment on renal and intestinal injuries after CA and resuscitation in pigs. Methods: Twenty-four male domestic pigs were randomly divided into one of the three groups: sham (n=6), CPR (n=10), or CPR+Alda-1 (n=8). CA was induced and untreated for 8 min, and then CPR was performed for 8 min in the CPR and CPR+Alda-1 groups. At 5 min after resuscitation, a dose of 0.88 mg/kg of Alda-1 was intravenously administered in the CPR+Alda-1 group. The biomarkers of renal and intestinal injuries after resuscitation were regularly measured for a total of 24 h. Subsequently, the animals were euthanized, and then renal and intestinal tissues were obtained for the measurements of ALDH2 activity and expression, and cell apoptosis and ferroptosis. Results: Five of the ten animals in the CPR group and six of the eight animals in the CPR+Alda-1 group were successfully resuscitated. After resuscitation, the levels of biomarkers of renal and intestinal injuries were significantly increased in all animals experiencing CA and resuscitation compared with the sham group; however, Alda-1 treatment significantly alleviated renal and intestinal injuries compared to the CPR group. Post-resuscitation ALDH2 activity was significantly decreased and its expression was markedly reduced in the kidney and intestine in those resuscitated animals compared with the sham group; nevertheless, both of them were significantly greater in those animals receiving Alda-1 treatment compared to the CPR group. In addition, renal, intestinal apoptosis and ferroptosis after resuscitation were observed in the CPR and CPR+Alda-1 groups, in which both of them were significantly milder in the CPR+Alda1 group than in the CPR group. Conclusions: The activation of ALDH2 by Alda-1 treatment significantly alleviated post-resuscitation renal and intestinal injuries through the inhibition of cell apoptosis and ferroptosis in a pig model of CA and resuscitation.